Effects of credit ratings on capital structure decisions before and after the Financial Crisis Year 2008 - JIANG, NING-YUAN (2018)
This paper aims to investigate the difference between credit ratings on firms’ capital structure choices both before and after the crisis year 2008. The sample includes 1014 listed firms in the USA during the period of 2003-2013. The sample period is divided into two parts, one is the pre-crisis period 2003-2007 and another one is the post-crisis period 2009-2013. This paper has three empirical tests. The first one investigates the leverage difference between firms with different credit levels and the difference has the tendency to decrease after the crisis year. Then the author would like to study whether high-quality firms have lower net debt issuance when compared with low-rated firms and whether the difference tends to decrease after the crisis year. The third one is that firms with the potential credit rating changes will issue lower debts both before and after the financial crisis year. The panel data models are used in this paper. The empirical tests results show that low-rated firms have lower leverage when compared with high-rate firms, the difference decreases after the crisis year because of the supply shock and investors’ risk preference. Apart from that, firms with lower ratings issue less net debt than high-rated firms, the difference has a reduction after 2008 as well. For firms approaching the credit ratio changes, they will have lower net debt issuance both before and after the crisis year. In general, the results of this paper are consistent with the existing literature, therefore they are reliable and trustworthy.